Prioritization of Farm Animal Welfare Issues Using Expert Consensus - Rioja-Lang, Fiona C.; Connor, Melanie; Bacon, Heather J.; Lawrence, Alistair B.; Dwyer, Cathy M. (Frontiers in Veterinary Science, 2020)
Prioritisation of animal welfare issues can help identify which areas most require research funding and raise awareness of best practices. A modified Delphi method was used to obtain expert opinion on the highest priority welfare issues for UK farmed livestock. Fifty-eight UK-based experts were recruited onto the study, with a minimum of 3 years experience of working with either cattle, pigs, poultry or small ruminants (12-16 experts per group). Experts were chosen to represent a broad range of opinions. Two rounds of surveys were conducted online using Online Survey, and the final round was an in-person workshop with 21 experts. In the first survey, experts were provided with a comprehensive list of species-specific welfare issues derived from the literature. Participants were asked to score each welfare issue, for i) severity, ii) duration, iii) prevalence on a 6-point Likert scale. The results of the first survey were reviewed and the welfare issues which scored a neutral-to-high response (scores 3-6) were carried forward. In round 2, participants were asked whether they agreed or disagreed with the rankings that were made from the results of round 1. The final stage of the process was a workshop, which consisted of a combination of group exercises and discussions, to reach the final consensus. Welfare priority lists were divided into two categories: severity/duration, and prevalence, to identify the priority welfare issues affecting individual animals and the population respectively. Across all farmed species common concerns were inadequate or inappropriate nutrition, inability of stockpeople to recognise or treat welfare issues (such as pain or behavioural problems), lameness, chronic or endemic health issues, euthanasia and mortality and morbidity of neonates. Specific concerns related to behavioural restriction and damaging or abnormal behaviour in pigs, poultry and dairy animals, inadequate housing for pigs and poultry, consequences of breeding decisions in pigs and poultry, and lack of access to veterinary care in sheep and beef. This Delphi process resulted in consensus on the most significant welfare challenges faced by UK livestock species and can help to guide future research and education priority decisions.